Phenotypic plasticity promotes persistence following severe events: physiological and morphological responses of seagrass to flooding - Maxwell, Paul S.; Pitt, Kylie A.; Burfeind, Dana D.; Olds, Andrew D.; Babcock, Russell C.; Connolly, Rod M. (The Journal of ecology, 2014)
1. Severe events such as floods or cyclones can have large ecological effects on the structure and functioning of ecosystems. The capacity of an ecosystem to adapt to, or absorb, the effects of a severe event depends on the severity and longevity of the event and the tolerance of the species present. 2. Seagrasses exhibit phenotypic plasticity at the plant to meadow scale through a variety of physiological and morphological acclimations to light stress to enhance photosynthetic capacity. These acclimations provide early warning of the possible risk of larger scale seagrass loss and can therefore be used in predicting how ecosystems might respond to severe events. 3. The physiological and morphological responses of 12 seagrass (Zostera muelleri) meadows to a severe flood were examined to test two main hypotheses: (i) that the physiological and morphological characteristics of seagrass would differ between meadows along the established chronic water quality gradient, in a pattern consistent with prior acclimations which have been shown to enhance photosynthetic capacity and (ii) that physiological and morphological responses to the flood would differ between meadows in a manner consistent with their position along the water quality gradient. 4. Meadows had different physiological and morphological characteristics across the water quality gradient, with meadows subject to chronically poorer water quality exhibiting characteristics consistent with those that maximize photosynthetic capacity. Despite a large discrepancy in impact among meadows, all meadows sampled responded consistently to the flood, exhibiting only physiological changes with no significant reduction in biomass. This suggests that photoacclimation to chronically poor conditions can enable seagrasses to withstand the effects of severe events, such as floods. 5. Synthesis. Phenotypic plasticity in habitat-forming species can result in a large variation in their responses to severe events, such as floods or cyclones. Acclimation to prior poor environmental conditions can promote persistence in habitat-forming species, such as seagrasses, following severe events. The measurement of phenotypic characteristics along an impact gradient can therefore provide an indication of the response of habitat-forming species to severe events.